NEUROPHYSIOLOGICAL ASPECTS OF THE BIOBEHAVIORAL THERAPY IN DISORDERS OF PERSONALITY - E. N. Zagoruyko; O. S. Shubina (Бюллетень сибирской медицины)
In this work the suggested method of biofeedback is one of those unique practices, which enables to find an individual approach to every patient, consider his character traits, and, in addition to this, the patient himself comes to realization of the problem, that is not so easy with personality disorders. Biofeedback therapy results not only in the change of physiological data, but also of cognitive stereotypes and behavioral patterns, which makes it possible to optimize the social, professional and interpersonal functioning of a patient.